Perubahan Iklim Danau Bandung Purba Berdasarkan Analisis Palinologi, Daerah Cihideung, Lembang, Jawa Barat - Rizki Satria Rachman; Winantris Winantris; Budi Muljana; Nana Sulaksana (Pusat Survei Geologi, 2020)
IClimate is the prevailing weather condition of an area throughout the year. Climate affects the vegetation in a region. The research aimed to study the climate and humidity change during the Holocene in Bandung Paleo-Lake based on palynomorph analysis. The twenty-four samples were taken using hand drill in 172.5 - 52.5 cm depth, continued with preparation and determination. In this study, descriptive analysis and comparison between pollen, spores and their sediments to show the climate and humidity change in Bandung Paleo-Lake. The results show that the samples which were taken on peat deposits showing four times climate changes in five zones, which characterized by montane forest pollens, i.e. Podocarpaceae and Pinaceae, lowland forest pollen i.e. Commelinaceae, Moraceae, spores from the Family Polypodiaceae, Pteridaceae and Dennstaedtiaceae, and Gramineae at the study area.Keywords: Climate, palaeo, analysis, palinology, Bandung Lake.